Remarks on paraconsistent decision making theory - Abe, J. M. (2003)
In this expository work we show how the para-analyzer can be useful to a variety of applications involving decision making when facing mainly with uncertainty, inconsistent or paracomplete information. The Para-analyzer can be implemented electronically, originating the Para-control, very useful in applications in the area of Robotics and Automation.